Evaluation Of Hydroxypropyl Methylcelluloe (HPMC) As A Tablet Coating Material Using Conventional Pan Coating - Alfadol, Khalid Ibrahim (2003)
Even though pharmaceutical coatings were once predominantly of the sugar coating variety, film coating has become the process of choice in the pharmaceutical industry today. In this study the suitability of hydroxypropyl methyl cellulose (HPMC)(Pharmacoat 606) as a tablet film-coating system was evaluated. The moisture permeability and mechanical properties of some aqueous free films were evaluated using permeability cell and stress-strain techniques respectively.